Eco-Friendly Management of Root Lesion Nematodes Using Volatile Allelochemicals - Gonçalo Pereira; Pedro Barbosa; Cláudia S. L. Vicente; Jorge M. S. Faria (Agronomy)
Root lesion nematodes (RLNs) are major plant parasites causing significant global yield losses in a wide range of crops. Current management strategies largely depend on synthetic nematicides, which raise environmental and human health concerns due to their broad-spectrum toxicity and persistence in the ecosystem. Volatile allelochemicals offer a promising, environmentally safer alternative due to their biodegradability and lower toxicity to mammals. In this study, we assessed the nematicidal activity of five allelochemical volatiles—dimethyl sulphide (DMS), dimethyl disulphide (DMDS), trans-cinnamaldehyde (TCA), trans-2-decenal (T2D), and trans-2-undecenal (T2U)—against Pratylenchus penetrans, using direct-contact bioassays, in comparison with the conventional nematicide oxamyl. Additionally, we assessed their environmental behaviour and toxicity profiles through in silico modelling. At 1 mg/mL, TCA, T2D, and T2U exhibited strong activity against P. penetrans, outperforming oxamyl by up to 1.6-fold, while DMS and DMDS showed reduced activity. The environmental risk assessment revealed that these compounds have a lower predicted persistence and bioaccumulation compared with oxamyl or fluopyram, a new generation nematicide. Though these findings boost the potential of these compounds as sustainable alternatives for RLN management, field validation and testing with non-target organisms remain necessary for the development of biopesticides. Nevertheless, this study emphasizes the need for an integrated risk-based assessment in the selection of nematicidal agents, warranting efficacy as well as environmental safety.